MOBILITY OF MERCURY IN THE VOLCANIC/GEOTHERMAL AREA OF NISYROS (GREECE) - Gagliano, A.L.; Calabrese, S.; Daskalopoulou, K.; Cabassi, J.; Capecchiacci, F.; Tassi, F.; Bonsignore, M.; Sprovieri, M.; Kyriakopoulos, K.; Bellomo, S.; Brusca, L.; D’Alessandro, W. (Bulletin of the Geological Society of Greece, 2016)
In the summer 2013, mercury concentrations in soils and air from Nisyros (Greece), an active volcanic island located in the Aegean Sea, were determined. Up to 102 samples of soil were collected in the Lakki plain caldera and analyzed for mercury by using a cold vapour atomic absorption analyzer, following 7473 US EPA method. Concentrations of mercury in air were also investigated in the same sites with a portable spectrophotometer (Lumex RA-915M). Soil mercury concentrations were in the range from 0.023 to 13.7 µg/g. The mercury concentrations in air showed high background values in the Lakki plain caldera, ranging from 21 to 36 ng/m3 and maximum values up to 493 ng/m3 in the proximity of the fumarolic areas, in contrast with the relatively low values (from 2 to 5 ng/m3 ) measured in the distal sites outside of the caldera. The positive correlation between mercury and CO2 and H2S in the atmosphere highlights the important role of fumarolic gases as carrier for gaseous mercury (Hg0 ). On the contrary, mercury does not show significant correlations with CO2 and H2S in the soil gases. This finding evidences the complexity of the processes affecting mercury in hydrothermal gases passing through the soil.